Advances in the Molecular Pathogenesis of Acute Myeloid Leukemia - Rusul Ahmed Mohammed; Nada Khazal K. Hindi; Mustafa Hussein Mohammed; Zahraa I. J. Shubber; Abdolmajid Ghasemian (Journal of Biomedicine and Biochemistry, 2026)
Acute Myeloid Leukemia comprises a heterogeneous group of clonal disorders that result from the abnormal accumulation of immature myeloid cells within the bone marrow and peripheral blood. This study aims to detect Advances in the Molecular Pathogenesis of Acute Myeloid Leukemia. This has been elucidated by recent molecular studies that identified crucial mutations in FLT3, NPM1, and DNMT3A genes and epigenetic changes that contribute to leukemogenesis. Deregulated pathways besides PI3K/AKT and MAPK have also asserted themselves in disease progression and resistance to therapy. Hence, the review presents an extensive discussion of contemporary molecular perspectives of AML pathogenesis and their relevance to diagnosis and treatment. The rise in targeted therapies and precision medicine thus paints a promising clinical picture for a better prognosis. Knowledge of the biological compromise unleashed by mutations in genes and their interplay with the bone marrow microenvironment is key to forging newer therapies.